Bad boy - Robinson, Peter, 1950- (Robinson, Peter, 1950- Inspector Banks series., 2011)
Detective Chief Inspector Alan Banks must face his most challenging and personal case yet. A distraught woman arrives at the Eastvale police station desperate to speak to Banks. Since he's away on holiday, his partner, Annie Cabbot, steps in. The woman tells Annie that she's found a loaded gun hidden in the bedroom of her daughter, Erin--a punishable offense under English law. When an armed response team breaks into the house to retrieve the weapon, the seemingly straightforward procedure quickly spirals out of control. But trouble is only beginning, for it turns out that Erin's best friend and roommate is none other than Tracy Banks, the DCI's daughter, who was last seen racing off to warn the owner of the gun, a very bad boy indeed. Now, Annie and Banks--a bit of a bad boy himself--must risk everything to outsmart a smooth and devious psychopath.--From publisher description.